A novel polymer based fluorimetric sensor for fast and selective determination of chlorpyrifos - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (ELSEVIER, 2021)
In this study, a spectrofluorometric method has been developed for the determination of chlorpyrifos. For this purpose, firstly, a polymer based membrane has been prepared for chlorpyrifos determination and parameters such as pH, calibration range, sensitivity, selectivity, sensitivity, response time and reproducibility were systematically investigated following the characterization of the membrane. Chlorpyrifos, an organophosphorus pesticide, can be determined by our sensor using the maximum excitation and emission wave lengths at 376 nm and 422 nm, respectively. The measurements can be completed within 20 s and the method also has a very low detection limit of 4.44 ? 10-10 mol L-1. Moreover, the developed polymeric Chlorpyrifos sensor is also suitable for the analysis of chlorpyrifos in tap water and pollen real samples.
Keywords: Chlorpyrifos; Cyclodextrin; Pesticide; Polymeric membrane; Sensor; Fluorimetry; ORGANOPHOSPHORUS PESTICIDES; VISIBLE-LIGHT; QUANTUM-DOT; DEGRADATION; SAMPLES; CHROMATOGRAPHY; HYDROLYSIS; INCLUSION; ACETYLCHOLINESTERASE; CYCLODEXTRINS